Reintegration, hospitality and hostility:Song-writing and song-sharing in criminal justice - Cathcart Froden, Lucy (2019)
Distant Voices is an ongoing, interdisciplinary collaborative action research project, drawing on criminology, community development, politics, practice-led research and songwriting to explore crime, punishment and reintegration through creative conversations that aim to challenge and unsettle understandings of and approaches to rehabilitation and reintegration. In this paper, we discuss some of the thinking behind the project and we reflect on our experiences to date as a community of enquiry. Specifically, we explore the extent to which certain practices of hospitality that we have experienced in processes of collaborative songwriting and song-sharing might mediate and resist the ‘hostile environment’ that faces people leaving prison in many contemporary societies. Drawing on our experience, we argue that hospitality is often disruptive; that creating and sustaining hospitable environments is extremely challenging; and that to do so requires careful thought and planning, including in relation to problems created by the power dynamics intrinsic to criminal justice. The paper includes links to and discussion of one song written in the project – ‘An Open Door’ -- which engages with and illustrates these themes